Morphometric Analysis of Upper Karha Watershed in Semi-Arid Area, Western Maharashtra, India: A quantitative analysis of the morphometric characteristics and drainage patterns in the Upper Karha watershed of Western Maharashtra, India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present work, an attempt has been made to study the quantitative geomorphological analysis of the Upper Karha watershed of Karha River Basin, Western Maharashtra, India. The study involves conventional top sheets, Geographic Information System (GIS) and Remote Sensing technique which are proved to be of immensely helpful to evaluate and compare linear relief and aerial morphometric features of a watershed. Morphological characteristics of the drainage line as appear in shape ,size, number, order, length, D, Rb, Fs, T, R are derived to trace its usefulness for surface development. Upper Karha watershed is basically 6th order drainage and mainly dendritic to sub dendritic. Drainage density and texture of the drainage basin is 3.13 kmkm c2, 17.591 respectively. The drainage frequency of Upper Karha watersheds is 4.31 whereas the bifurcation ratio ranges from 3 to 5.